MAIN DIRECTIONS AND TRENDS OF AGRICULTURAL FINANCING (American Journal of Interdisciplinary Research and Development, 2023)
The article examines the opinions of the world's leading scientists on the main directions and trends of agricultural financing, the current state of agricultural financing in the economy of Uzbekistan, the volume of investments made in this sector and the absorption of them in the cross-section of sectors, and the development of justified conclusions and proposals for the improvement of agricultural financing. developed and recommendations for application in our country.